2021
DOI: 10.3390/molecules26092469
|View full text |Cite
|
Sign up to set email alerts
|

LC-HRMS Profiling and Antidiabetic, Anticholinergic, and Antioxidant Activities of Aerial Parts of Kınkor (Ferulago stellata)

Abstract: Kınkor (Ferulago stellata) is Turkish medicinal plant species and used in folk medicine against some diseases. As far as we know, the data are not available on the biological activities and chemical composition of this medicinal plant. In this study, the phytochemical composition; some metabolic enzyme inhibition; and antidiabetic, anticholinergic, and antioxidant activities of this plant were assessed. In order to evaluate the antioxidant activity of evaporated ethanolic extract (EEFS) and lyophilized water e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 97 publications
0
39
0
Order By: Relevance
“…Recently, it was shown that 6.7 and 4.9 mg of QE flavonoids were found in g lyophilized water and evaporated ethanolic extracts of Ferula orientalis. [2] Also, 27.30 and 11.75 mg QE of flavonoids was found for ethanolic and water extracts Convulvulus betonicifolia, respectively. [3] Similarly, it was shown that 1.480 and 0.328 mg of QE flavonoids per 1 g dried extracts were found in ethanol and water extracts of avocado.…”
Section: Polyphenolic Compositionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, it was shown that 6.7 and 4.9 mg of QE flavonoids were found in g lyophilized water and evaporated ethanolic extracts of Ferula orientalis. [2] Also, 27.30 and 11.75 mg QE of flavonoids was found for ethanolic and water extracts Convulvulus betonicifolia, respectively. [3] Similarly, it was shown that 1.480 and 0.328 mg of QE flavonoids per 1 g dried extracts were found in ethanol and water extracts of avocado.…”
Section: Polyphenolic Compositionmentioning
confidence: 86%
“…However, Turkey has a wide plant biodiversity for use in these areas. [2,3] Also, biologically active secondary metabolites are a large group of chemicals with small molecular weights and widely used in folk medicine for their well-known potential for biological, chemical and physiological abilities including anti-inflammatory, antidiabetic, neuroprotective and antioxidant features. [4,5] The Lamiaceae family is a large plant family with hundreds of biologically active secondary plant metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme hydrolyzes carbohydrates by acting on 1,4-α bonds and releases D-glucose from the nonreducing end of the sugar. [37][38][39] It plays a key role in carbohydrate metabolism in plants, animals, and microorganisms. It is quite common in microorganisms and has been characterized by purifying its extracellular, intracellular, or cell-bound forms from various bacteria, yeasts, and molds.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants have been shown to play a crucial role in delaying or avoiding T2DM and AD [ 9 ]. One of the main goals in the treatment of T2DM is to provide inhibition studies of α-glycosidase, which is one of the most important digestive enzymes and catalyzes the breakdown of dietary polysaccharides [ 10 ].…”
Section: Introductionmentioning
confidence: 99%